Analisis Pengelolaan Retribusi Pasar Di Kota Rembang Dalam Meningkatkan Pendapatan Asli Daerah Kabupaten Rembang Tahun 2023 - Pentanurbowo, S; Uyun, Jazila Syifaul (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Market retribution is a fee set by the local government for traders in markets, including both traditional and modern markets. Rembang City Market is a significant trading center in the economy of Rembang Regency. However, market retribution revenue in the city has not met the set targets due to a lack of awareness among traders about paying retribution and challenges in market management systems and the human resources managing the market retribution. The research method used is descriptive with a qualitative approach. The analysis results show that in 2023, market retribution revenue only reached 68% of the target, amounting to IDR 1,262,295,250 out of the target of IDR 1,863,066,201. Challenges such as a lack of trader awareness and technical issues in retribution payment using electronic cards, including errors in retribution devices and signal disruptions, have led to an increase in retribution payment arrears. As a result, the achievement of market retribution targets and local revenue of rembang regency in 2023 has decreased.